Enhancing Council Accountability and Performance Through Internal Audit in The Gambia and Sub-Saharan Africa - Lamin K Drammeh; Nazaruddin Malik; Driana Leniwati (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
Purpose: This paper examines the role of internal audit in accountability and performance in local government councils in The Gambia where the reforms of a decentralisation has enlarged the mandates without corresponding governance capacity. It bridges the gap in the empirical and theoretical literature by examining the effectiveness of internal audit at the sub-national level and deriving comparative lessons of African countries. Method: The qualitative research design was applied. They were semi-structured interviews with 26 officials, structured qualitative surveys and document analysis of audit reports and policy documents. The data were coded using open and axial and selective coding, cross-source triangulation to reveal institutional, political and operational forces which influence internal audit practices. Findings: The internal audit units lack independence, capacity, and ability to impact on procurement, budgeting, and service delivery decisions due to limited independence, capacity, and political interference. The challenges in developing countries are similar, and the ones peculiar to Gambia are the CEOs-controlled reporting lines and the administrative culture of the hierarchies. Observations in other countries such as Kenya, Ghana and South Africa reveal that independent audit committees and performance audit practices as well as statutory enforcement mechanisms enhance the utilisation and accountability results of audit. Implications: To improve internal audit, reforms that will improve the independence of auditors, institutionalise the follow up procedures, and the implementation of audit recommendations is necessary. All these are needed to reduce internal audit operations into concrete gains in accountability and council performance. Novelty/Value: This research is among the earliest qualitative evaluations of internal audit systems in Gambian local councils. It combines institutional and principal-agency theory and African comparative experience to suggest situation-specific avenues of enhancing accountability in decentralised governance settings.